Of an Alien Homecoming : Reading Heidegger's Hölderlin. - Bambach, Charles R. (Albany : State University of New York Press, 2022)
The first book-length study in English of the Heidegger-Hölderlin relation, addressing the tension between Heidegger's political commitments during National Socialism and Hölderlin's ideal of poetic dwelling.
Front Matter -- Contents -- Abbreviations -- Acknowledgments -- Preface -- Introduction -- Hölderlin's Hymns "Germania" and "The Rhine" -- Heidegger's "Remembrance" Lectures -- Heidegger's "Ister" Lectures -- Historical Interlude -- Heidegger in Dialogue with Hölderlin " -- Postscript -- Notes -- Bibliography -- Index
JSTOR
Keywords: Heidegger, Martin, -- 1889-1976.; Hölderlin, Friedrich, -- 1770-1843.; Heidegger, Martin, -- 1889-1976 -- Influence; Hölderlin, Friedrich, -- 1770-1843 -- Influence; Heidegger, Martin, -- 1889-1976; Hölderlin, Friedrich, -- 1770-1843; National socialism; Political science -- Philosophy; Nazisme; National Socialism; PHILOSOPHY / General; Influence (Literary, artistic, etc.); National socialism; Political science -- Philosophy; Rezeption